Preparation and oxidation resistance of polyphenylene sulfide modified by high-temperature antioxidants. (14th April 2021) - Xing, J; Xu, Z Z; Li, D W
Abstract: Two types of high-temperature antioxidants (Revonox 608 and GA-80) were used to improve the oxidation resistance of polyphenylene sulfide (PPS) through melt blending, and the resistance against oxidation and other properties were characterized. The results showed that GA-80 exhibited better dispersibility and compatibility with the PPS matrix than did Revonox 608. Revonox 608 could act as a heterogeneous nucleation agent that can promote crystallization and improve the crystallinity of PPS, whereas GA-80 could delay the movement of chain segments and limit crystallization. The thermal-oxidative stability of PPS can be improved by adding antioxidants due to prior oxidative decomposition. The dynamic oxidation induction temperature of PPS increased by more than 10 °C because of the capture of free radicals and the decomposition of hydroperoxides by antioxidants. The XPS results showed that both GA-80 and Revonox 608 could retard the oxidative cleavage of the C-S-C bond in the PPS macromolecular chains and protect the S atoms from oxidizing to sulfone groups.